Initiation of non-invasive ventilation in amyotrophic lateral sclerosis and clinical practice guidelines: Single-centre, retrospective, descriptive study in a national reference centre. Issue 1 (2nd January 2017) - Georges, Marjolaine; Golmard, Jean-Louis; Llontop, Claudia; Shoukri, Amr; Salachas, François; Similowski, Thomas; Morelot-Panzini, Capucine; Gonzalez-Bermejo, Jésus
Abstract: In amyotrophic lateral sclerosis (ALS), respiratory muscle weakness leads to respiratory failure. Non-invasive ventilation (NIV) maintains adequate ventilation in ALS patients. NIV alleviates symptoms and improves survival. In 2006, French guidelines established criteria for NIV initiation based on limited evidence. Their impact on clinical practice remains unknown. Our objective was to describe NIV initiation practices of the main French ALS tertiary referral centre with respect to guidelines. In this retrospective descriptive study, 624 patients followed in a single national reference centre began NIV between 2005 and 2013. We analysed criteria used to initiate NIV, including symptoms, PaCO2, forced vital capacity, maximal inspiratory pressures and time spent with SpO2 <90% at night. At NIV initiation, 90% of patients were symptomatic. Median PaCO2 was 48 mmHg. The main criterion to initiate NIV was 'symptoms' followed by 'hypercapnia' in 42% and 34% of cases, respectively. NIV was initiated on functional parameters in only 5% of cases. Guidelines were followed in 81% of cases. In conclusion, despite compliance with French guidelines, the majority of patients are treated at the stage of symptomatic daytime hypoventilation, which suggests that NIV is initiated late in the course of ALS. Whether this practice could be improved by changing guidelines or increasing respiratory-dedicated resources remains to be determined.